Production, optimization and characterization of L-glutaminase from marine bacteria - Nur Dini, Johari (2019)
L-glutaminase present in living organisms. L-glutaminase has been identified having potential applications for several industries including pharmaceutical, food, and health care. However, industrial sectors nowadays demand natural producing enzyme compared to artificial enzymes. L-glutaminase extracted from microorganisms has more advantages to fulfil demands from industries. Up until now, less research about bacterial production of L-glutaminase from local marine environments had been carried out. Hence, the study aims to investigate the L-glutaminase production, optimization and characterization of partially-purified L-glutaminase from bacterial isolates of local marine environment. In this study, the screening of bacteria-producing L-glutaminase had been implemented from three different Pahang Beaches known as Pantai Teluk Cempedak, Pantai Batu Hitam, and Pantai Balok. A total of 17 isolates showed positive response on production of L-glutaminase. However, only 12 isolates showed positive response with strong colour change which then proceeded for biochemical characterization and 16S rRNA sequence analysis. The biochemical characterizations analysis showed negative results for all tests that had been carried out. Then, 16S rRNA gene sequencing were further proceeded to identify the identity of bacteria that showed positive results on L-glutaminase production. Additionally, production, optimization, enzyme purification and characterization were carried out from the best L-glutaminase producer. The two highest enzyme activity recorded was from Kosakonia radicincitans with enzyme activity of 0.103 U/ml and Shigella flexneri which has the enzyme activity of 0.100 U/ml. Furthermore, two isolates that had the highest enzyme activity were selected for optimization of process parameters through One Factor at A Time method. The parameters involved are temperature, pH, additional of organic and inorganic nitrogen sources, and additional of carbon sources. It was found out that K. radicincitans and S. flexneri have the highest enzyme activity at temperature 37°C, pH 7, additional of ammonium chloride as inorganic nitrogen source, and additional of glucose for carbon source. However, K. radicincitans has the highest enzyme activity when beef extract was added to its culture media while S. flexneri prefer yeast extract. An experiment with all parameters at its optimal level was conducted and K. radicincitans had the highest enzyme activity of 0.3542 U/ml at temperature of 37°C, pH 7, additional of beef extract for organic nitrogen source, additional of ammonium chloride for inorganic nitrogen source, and additional of glucose as the carbon source. Lglutaminase extracted from K. radicincitans was further partially purified and characterized. It had a molecular weight of 70 kDA. L-glutaminase was most reactive and stable at temperature of 37ºC and pH 7. This knowledge on production, optimization, and characterization of L-glutaminase are very important in order to understand its characteristics and suitability for industrial usage.